De-studentification: emptying housing and neighbourhoods of student populations. (August 2016) - Kinton, Chloe; Smith, Darren P; Harrison, John
International scholarship on student geographies and urban change continues to advance knowledge of the intense commodification of student lifestyles and student housing. The main aim of this paper is to consider some of the hitherto under-researched wider knock-on effects of more commodified student housing markets. Here we present findings from the first-ever empirical study of de-studentification. Using the case study of Loughborough, we demonstrate how de-studentification is a process of change that has been stimulated by the increased supply of purpose-built student accommodation. We show that de-studentification leads to the depopulation and decline of some classical studentified neighbourhoods. Moreover, these urban transformations have several significant implications for pre-existing conceptualisations of urban change and student geographies. Notably, the impacts of de-studentification pose important questions for the conceptual boundaries of studentification – a prerequisite of de-studentification – and although, to date, dominant conceptualisations of studentification are wedded to upgrading-led representations of urban gentrification, it is shown that de-studentification, conversely, leads to physical downgrading and emptying of neighbourhoods in distinct phases. We therefore argue for a process-led definition of de-studentification, to illustrate how studentified neighbourhoods are gradually 'emptied' of student populations and student housing. More broadly, it is asserted that new student geographies are being created by the deepening neoliberalisation and commodification of higher education, which, in turn, will have unintentional consequences for wider social, cultural and economic relations in university towns and cities, such as emergent community cohesion and changing senses of place.